A replication study testing the validity of AR simulation in VR for controlled experiments - Lee, Cha; Bonebrake, Scott; Hollerer, Tobias; Bowman, Doug A. (2009 8th IEEE International Symposium on Mixed and Augmented Reality, 2009)
It is extremely challenging to run controlled studies comparing multiple Augmented Reality (AR) systems. We use an “AR simulation” approach, in which a Virtual Reality (VR) system is used to simulate multiple AR systems. In order to validate this approach, we carefully replicated a well-known study by Ellis et al. using our simulator, obtaining comparable results.